Total Phenolic, Flavonoid Contents, and Antioxidant Activities of Different Parts of Malus domestica L. in Iraq - Zainab Yaseen Mohammed Hasan (Iraqi Journal of Pharmaceutical Sciences)
The current study was designed to estimate the qualitative and quantitative analyses of total phenolic and flavonoid compounds extracted by two different techniques (maceration and soxhlet) for three aerial parts (leaves, stems, and petioles) of Malus domestica grown naturally in Iraq. A general phytochemical investigation of the three parts of the plant had been carried out before the extraction process. Qualitative estimation was held through the Thin Layer Chromatographic Technique to visualize separated fluorescent spots as proposed phenolic and flavonoid compounds corresponding to standard compounds. Total Phenolic Content (TPC) and Total Flavonoid Content (TFC) were determined by colorimetric methods and by HPLC method. The free radical scavenging assay for (DPPH) was carried out to measure antioxidant activity for all extracted portions. Phytochemical screening of the three parts of Malus domestica showed the presence of different active constituents such as saponins, tannins, alkaloids, terpenoids, flavonoids, polyphenols, and glycosides. The maceration extraction technique resulted in a higher yield for all fractions compared to the Soxhlet technique. The results also showed a variation in the phenolic compounds among the different parts, revealing that the leaves of Malus domestica had a high content of phenolic acids and flavonoids compared to the other parts, while the petioles (extracted by soxhlet) showed the strongest antioxidant activity (86.01 %) compared to other parts. Based on HPLC assay, the components obtained from leaves, stems, and petioles ethanolic extract were declared to contain 7 phenolic acids (including ascorbic acid, gallic acid, vanillic acid, chlorogenic acid, p-coumaric acid, caffic acid, and ferulic acid). Whereas, 10 flavonoids (including rutin, quercetin, myricetin, catechin, kaempferol, hispartin, isorhamnetin, apigenin,coumarin and  luteolin) were identified.